Agent and Multi-Agent Systems: Technology and Applications 10th KES International Conference, KES-AMSTA 2016 Puerto de la Cruz, Tenerife, Spain, June 2016 Proceedings - Jezic, Gordan; Chen-Burger, Yun-Heh Jessica; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The modern economy is driven by technologies and knowledge. Digital technologies can free, shift and multiply choices, often intruding on the space of other industries, by providing new ways of conducting business operations and creating values for customers and companies. The topics covered in this volume include software agents, multi-agent systems, agent modelling, mobile and cloud computing, big data analysis, business intelligence, artificial intelligence, social systems, computer embedded systems and nature inspired manufacturing, etc. that contribute to the modern Digital Economy. This volume highlights new trends and challenges in agent, new digital and knowledge economy research and includes 28 papers classified in the following specific topics: business process management, agent-based modeling and simulation, anthropic-oriented computing, learning paradigms, business informatics and gaming, digital economy, and advances in networked virtual enterprises. Published papers were selected for presentation at the 10th KES Conference on Agent and Multi-Agent Systems: Technologies and Applications (KES-AMSTA 2016) held in Puerto de la Cruz, Tenerife, Spain. Presented results would be of theoretical and practical value to researchers and industrial practitioners working in the fields of artificial intelligence, collective computational intelligence, innovative business models, new digital and knowledge economy and, in particular, agent and multi-agent systems, technologies, tools and applications.
Part I: Agent and Multi-Agent Systems -- Part II: Agent-based Modeling and Simulation -- Part III: Business Process Management -- Part IV: Learning Paradigms and Applications: Agent-based Approach -- Part V: Anthropic-Oriented Computing (AOC) -- Part VI: Business Informatics and Gaming through Agent-based Modelling.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence